Tecendo competências na educação profissional: a metodologia de ensino por competências no curso técnico têxtil da escola Senai Francisco Matarazzo em São Paulo - 2003-2011 - Menezes, Alexsandra Maria dos Santos (2012)
This dissertation is the result of a study on professional education in the context of restructuring the curriculum for training and skills certification. It is believed that only their institutionalization can not offer subsidies for the organization pedagogical practice. So, the research seeks to identify the teaching practice, elements that can contribute to the realization of the proposal. This model curriculum is not a new proposal, but its institutionalization, when transformed in practice, brings nuances to the particularity giving differentiated teaching. Since the teacher greater concretizing of regulatory changes, it is believed that the from practice can identify and understand the actions and adaptations made by institution to assist the teacher in the learning process. It is intended that this study will contribute to a reflection on the use of referential debate comptências of vocational education. For this, a survey was conducted, with teachers and a school coordinator SENAI in São Paulo, and to check understand, what significant changes in pedagogical practice of technical course professional, in the form of subsequent textile area. In this process, the teacher highlighted as an articulator of normative principles and values, institutional and subjective of each student. In implementing this curriculum, we identified some limitations regarding the management of the educational process, or initial and continuing teacher education and reach of institutional goals, as well as improvement of the process teaching, or difficulties of students from basic education.